Barriers to social workers practice of clinical skills in health care (A descriptive study applied to social workers working in hospitals in the Riyadh region) - Alhwymel, Omar Mohammed (Journal of Humanities & Social Sciences, 2022)
The study aimed at the most important obstacles to social workers' practice of clinical skills in the field of health care (institution, institution, client). And their number reached (81) specialists. Tool The trading tool is practiced on hospitals in the Riyadh region by sending the electronic link to the financial tool. The researcher obtained the responses of all the study competition by (81) questionnaires. The statistical program (spss), and start analyzing it, drawing conclusions and interpreting them.The study found a set of results, the most important of which are: One of the most important obstacles that are due to social workers when practicing clinical skills is (social workers’ preoccupation with administrative work and distance from professional work, as well as the social worker’s lack of knowledge of what is new in the field of individual service, especially with regard to skills clinical)The results also showed that one of the most important obstacles attributed to the institution is (the hospital administration does not understand many of the responsibilities and tasks of the social worker, as well as the lack of recognition by some officials of the experiences and skills of the medical social worker in the hospital).The results of the study also showed one of the most important obstacles due to the client is (the client’s neglect of the advice and directions of the social worker, and the patient’s concealment of his illness from others due to its association with shame or stigma).The study recommended the need to increase the general budget of the hospital and provide financial incentives to the social worker, as well as the need to work on developing awareness of the importance of the role of social service in the medical field.
Keywords: role; clinical social worker; skill; obstacles; Health care